A novel molecular synthesis route to Li2S loaded carbon fibers for lithium–sulfur batteries. Issue 18 (5th April 2022) - Brune, Veronika; Bohr, Christoph; Ludwig, Tim; Wilhelm, Michael; Hirt, Sebastian Daniel; Fischer, Thomas; Wennig, Sebastian; Oberschachtsiek, Bernd; Ichangi, Arun; Mathur, Sanjay
Abstract : A novel simple synthetic pathway to a carbon-coated Li2 S material from a single molecular source for battery application using electrospinning methods is presented. Abstract : The synthesis of a novel air-stable molecular precursor (LiSC2 H4 )2 NMe enables the formation of the desired 1D lithium sulfide (Li2 S) via the electrospinning method under ambient conditions. The solubility of the precursor in polar solvents combined with a common polymer (PVP) allowed a suitable spinning solution to obtain ideal green Li2 S loaded fibers. 3D fiber mats of the calcined homogeneous 1D electrospun Li2 S/C fibers were characterized by electron microscopy and X-ray powder diffraction analysis. Direct integration of Li2 S in an electronically conductive carbon matrix as the cathode obviates the need of elemental lithium as the anode, which is a great advantage against the reported lithium–sulfur batteries. An initial capacity of about 870 mA h g −1 at C/20, a capacity retention of 73% after 100 cycles at C/10 and a capacity of about 400 mA h g −1 at 1C were observed for the presented system.